2014
DOI: 10.1002/2014ja019831
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of CIR‐ and CME‐induced geomagnetic activity on thermospheric densities and spacecraft orbits: Statistical studies

Abstract: Enhanced energy input from the magnetosphere to the upper atmosphere during geomagnetic storms has a profound effect on thermospheric density and consequently near-Earth satellite orbit decay. These geomagnetic storms are caused by two different processes. The first is coronal mass ejections (CMEs) and the second is corotating interaction regions (CIRs). CME-driven storms are characterized by large maximum energy input but relatively short duration, whereas CIR-driven storms have relatively small maximum energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 32 publications
7
42
0
Order By: Relevance
“…Above this value, we recognize larger scattering and some indication of saturation. The lower correlation between the AE index and the thermospheric densities is in agreement with previous findings [Akasofu et al, 1983;Baumjohann, 1986;Chen et al, 2014]. These authors revealed some limitations concerning the measured quantity (H field), the existence of longitudinal gaps and the small latitudinal range of the contributing observatories.…”
Section: Resultssupporting
confidence: 91%
“…Above this value, we recognize larger scattering and some indication of saturation. The lower correlation between the AE index and the thermospheric densities is in agreement with previous findings [Akasofu et al, 1983;Baumjohann, 1986;Chen et al, 2014]. These authors revealed some limitations concerning the measured quantity (H field), the existence of longitudinal gaps and the small latitudinal range of the contributing observatories.…”
Section: Resultssupporting
confidence: 91%
“…CIR‐ and CME‐driven storms can be classified based on the features of proton temperature, solar wind speed, magnetic field, and proton density (e.g., Richardson & Cane, ). CME‐driven storms can be identified by the stronger magnetic field, the enhanced solar wind speed, low proton temperature, and high ratio between the densities of alpha particles and protons (Chen et al, ; Gonzalez et al, ; Huttunen et al, ). Figure shows an example of a geomagnetic storm driven by CME during 15–20 March 2015.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the main features of CIR‐driven storms are an enhancement of proton temperature, an increase of solar wind speed, a compression of magnetic field, Bz component fluctuates throughout interval due to high‐speed streams, and proton density increases to unusually high values (e.g., Chen et al, ; Mavromichalaki et al, ; Xystouris et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These recurrent geomagnetic activities can perturb the ionosphere and thermosphere on a global scale as a result of energy and momentum deposition [ Lei et al ., ; Thayer et al ., ; Wang et al ., ; Burns et al ., ; Solomon et al ., ; Verkhoglyadova et al ., ]. As CIR and high‐speed stream‐induced geomagnetic activity can last for a long period of time (up to 27 days) due to the continuous Alfvén fluctuations within the high‐speed stream proper [ Tsurutani and Gonzalez , ; Tsurutani et al ., , ], the resulting total thermospheric density and satellite orbit perturbations can be larger than those produced by major geomagnetic storms associated with coronal mass ejections, [ Chen et al ., , ].…”
Section: Introductionmentioning
confidence: 99%